Penggunaan Probiotik Alami Berbahan Rempah pada Tambak Tradisional Blandongan, Kota Pasuruan - Kartikaningsih, Hartati; Koentjoro, Maharani Pertiwi; Sudaryanti, Sri; Anggraeni, Ike Listya; Gunawan, Fahdynia Karnira; Ashari, Fadhil Muhamad (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2025)
Traditional farmers in Pasuruan City face challenges in increasing pond productivity due to declining land quality and reliance on natural feed. Milkfish growth is often hampered by lack of feed and increased disease due to environmental changes. Although manufactured feed and probiotics are available, they are too expensive for traditional farmers. Pasuruan City has great potential for the development of milkfish farming, and the Banyu Urip Fish Farmers Group (POKDAKAN) is an experienced community in this field. The use of probiotics made from spices, such as ginger, turmeric, and curcuma, is proposed as an eco-friendly and economical solution as these ingredients are abundant and effective in improving pond water quality and fish disease resistance. The results of probiotic application showed significant improvement, with 85% of farmers reporting up to 30% increase in production, and 90% recording a decrease in fish disease cases. Pond water quality also improved, particularly in ammonia and dissolved oxygen levels. The use of this natural probiotic not only positively impacts the pond environment, but also supports the sustainability of milkfish farming productivity in Pasuruan City.